Design, synthesis and biological evaluation of benzamide derivatives as novel NTCP inhibitors that induce apoptosis in HepG2 cells. Issue 19 (1st October 2019) - Zhao, Shuangmei; Zhen, Yongqi; Fu, Leilei; Gao, Feng; Zhou, Xianli; Huang, Shuai; Zhang, Lan
Graphical abstract: Abstract: Sodium taurocholate cotransport polypeptide (NTCP) plays an important role in the development of hepatitis and acts as a switch to allow hepatitis virus to enter hepatic cells. As the entry receptor protein of hepatitis virus, NTCP is also an effective target for the treatment of hepatocellular carcinoma. Herein, twenty-five benzamide analogues were synthesized based on the virtual screening design and their anti-proliferative activities against HepG2 cells were evaluated in vitro . Compound 35 was found to be promising, with an IC50 value of 2.8 μM. The apoptosis induced by 35 was characterized by the regulation of markers, including an increase in Bax, cleaved-caspase 3, and cleaved-PARP proteins, and a decrease in Bcl-2 protein. Molecular docking and molecular dynamics (MD) simulation confirmed that compound 35 can bind tightly to NTCP. Western blot analysis also showed that NTCP was inhibited. Altogether, these results indicate that compound 35 acts as a novel NTCP inhibitor to induce apoptosis in HepG2 cells.